2013
DOI: 10.1007/s00421-013-2746-0
|View full text |Cite
|
Sign up to set email alerts
|

The influence of acetaminophen on repeated sprint cycling performance

Abstract: Acetaminophen may have improved performance through the reduction of pain for a given work rate, thereby enabling participants to exercise closer to a true physiological limit. These results suggest that exercise may be regulated by pain perception, and that an increased pain tolerance can improve exercise performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
7
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(95 citation statements)
references
References 42 publications
5
82
7
1
Order By: Relevance
“…For instance, previous research has shown that paracetamol improves performance in a 10-mile cycling time trial compared to placebo in the absence of a reduction in perceived pain or perceived exertion 3 . In another study, Foster et al 25 , also found that paracetamol improved performance compared to placebo.…”
Section: Discussionmentioning
confidence: 91%
“…For instance, previous research has shown that paracetamol improves performance in a 10-mile cycling time trial compared to placebo in the absence of a reduction in perceived pain or perceived exertion 3 . In another study, Foster et al 25 , also found that paracetamol improved performance compared to placebo.…”
Section: Discussionmentioning
confidence: 91%
“…Changes in work rate are made so as to moderate the level of pain and discomfort perceived, with reductions in work rate to manage the increase in pain, and increases in work rate to increase pain to a level that the athlete is willing to endure. These suggestions are supported by work that has used analgesia during self-paced exercise to improve performance 24,41. In these studies, cyclists appear to exercise according to a set progression of pain, with changes in work rate used to maintain this.…”
Section: Perspectivesmentioning
confidence: 94%
“…Consequently, moderate levels of induced pain may have little effect on short-duration or short-term voluntary contraction exercise, but elicit a large effect in long-duration exercise. Indeed, the effect of inducing experimental pain on short-duration exercise has produced equivocal results,4649 whereas in exercise that lasts for long periods, increased or decreased pain frequently worsens or improves endurance performance, respectively 24,41,45. The difficulties associated with testing the exercise-induced pain hypothesis (ie, by experimentally increasing or decreasing pain) may contribute towards these differing findings.…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Small, unblinded studies typically involving non-elite subjects have suggested that paracetamol can improve time to exhaustion260 or decrease perceived exertion in a graded run 261 262. NSAIDs have no effect on sprinting,263 vertical jumping or endurance running performance but can decrease soreness 2 263–265. Opioids can decrease pain265 and increase anaerobic performance265 but not overall physical performance after muscle damage 265.…”
Section: Antidoping Issues In Pain Managementmentioning
confidence: 99%